Determining conditions for the inner rotor profile of a hypogerotor lubrication pump - Truong Cong Giang; Nguyen Hong Thai (Journal of Technical Education Science, 2020)
Lubrication pumps for internal combustion engines of cycloid gear in general and hypogerotor in particular are being researched by many domestic and foreign researchers to improve working quality and perfect the design theory. However, the previous studies have not paid attention to the overlap of the profile from dedendum to addendum of the inner rotor and the collision between inner rotor and outer rotor during the working process. As a result, the designer must check manually and cannot automate the design and take a lot of time. This is the problem that the authors solve in this article.